2019
DOI: 10.1101/19008896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic value of the Residual Cancer Burden index according to breast cancer subtype: validation on a cohort of BC patients treated by neoadjuvant chemotherapy

Abstract: Introduction: The Residual Cancer Burden (RCB) quantifies residual disease after neoadjuvant chemotherapy (NAC). Its predictive value has not been validated on large cohorts with long term follow up. The objective of this work is to independently evaluate the prognostic value of the RCB index depending on BC subtypes (Luminal, HER2 positive and triple negative (TNBCs)). Methods: We retrospectively evaluated the RCB index on surgical specimens from a cohort of T1T3NxM0 BC patients treated with NAC between 2002 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…These therapy-tolerant cells can evolve either due to the selection of pre-existing resistant clones or via a significant molecular reprogramming during treatment that results in a cellular adaptive response (26,41,73). Several studies have independently affirmed that TNBC tumors recurrence rates are substantially higher in patients with residual disease and residual tumor burden is a very strong indicator of worst event free survival in TNBC patients worldwide (14,(74)(75)(76)(77)(78)(79)(80). Our cellular modeling of DTPs using different classes of chemotherapeutics supports the consolidated clinical observation as we have observed that TNBC cells have a high potential to overcome the drug induced stress condition as DTP and attain aggressive PDTP state, a feature that is independent of the molecular subtype.…”
Section: Discussionmentioning
confidence: 99%
“…These therapy-tolerant cells can evolve either due to the selection of pre-existing resistant clones or via a significant molecular reprogramming during treatment that results in a cellular adaptive response (26,41,73). Several studies have independently affirmed that TNBC tumors recurrence rates are substantially higher in patients with residual disease and residual tumor burden is a very strong indicator of worst event free survival in TNBC patients worldwide (14,(74)(75)(76)(77)(78)(79)(80). Our cellular modeling of DTPs using different classes of chemotherapeutics supports the consolidated clinical observation as we have observed that TNBC cells have a high potential to overcome the drug induced stress condition as DTP and attain aggressive PDTP state, a feature that is independent of the molecular subtype.…”
Section: Discussionmentioning
confidence: 99%